Effects of Midwifery Care on Mode of Delivery, Duration of Labor and Postpartum Hemorrhage of Elderly Parturients - Yuefang ZHOU; Chunping YANG (Tehran University of Medical Sciences, 2020)
Background: We aimed to explore the influence of midwifery care on the mode of delivery (MOD), duration of labor and postpartum hemorrhage (PPH) of elderly parturients. Methods: A total of 165 elderly parturients admitted to Tongde Hospital of Zhejiang Province, China from May 2018 to Aug 2019 were allocated into a study group (n=85, midwifery care) and a control group (n=80, conventional nursing care). Visual analogue scale (VAS) was employed to estimate the pain of parturients, and self-rating anxiety scale (SAS) and self-rating depression scale (SDS) were employed to evaluate the anxiety and depression status. The satisfaction of patients on nursing care was scored by a self-made satisfaction questionnaire. Results: The parturients in the study group presented higher spontaneous vaginal delivery (SVD) rate (P < 0.05), and had shortened duration of first and second stages of labor and total duration of labor (P < 0.05). The incidence of both PPH and neonatal asphyxia in the study group was lower than that in the control group (both P < 0.05). The VAS, SAS and SDS scores in the study group were significantly lower than those in the control group (P < 0.05), and the patients' satisfaction in the study group was significantly higher (P < 0.05). Conclusion: Midwifery care is effective for the delivery of elderly parturients, which significantly improves VSD rate, shortens duration of labor, reduces incidence of PPH and neonatal asphyxia, as well as relives labor pain, anxiety and depression, and increases satisfaction of parturients.